PRODUK GEL HAND SANITIZER BERBAHAN DASAR EKSTRAK CAIR DAUN SIRIH HIJAU (Piper betle Linn.) SEBAGAI ANTISEPTIK - Aznury, Martha; ., Sofiah; Sari, Rezki Prima (Politeknik Negeri Sriwijaya, 2020)
The rise of epidemics caused by microorganisms such as SARS, bird flu, HIV and COVID-19 has made people use products that contain antiseptics such as soap and hand sanitizers. However, in general, the basic ingredient for making antiseptics comes from alcohol. If you use it continuously, it will dissolve the layer of fat and sebum on the skin so that the skin becomes sensitive, dry and irritated. Antiseptic product development can be done with natural ingredients such as utilizing green betel leaf extract (Piper betle Linn.). It is known that green betel leaf (Piper betle Linn.) Has long been used in traditional medicine and can be a natural antiseptic ingredient for the manufacture of hand sanitizer gel. This study aims to determine the effect of green betel leaf on the antiseptic power in hand sanitizer gel preparations. The materials used in this study were carbomer 940, triethanolamine (TEA), glycerin, sodium metabisulfate, aquadest, and green betel leaf extract obtained from the soybean extraction process. The research was conducted by varying the betel leaf extract 0%, 10%, 20%, 30%, 40%, 50%, 60%, and 70%. The test was carried out by including organoleptic observations (shape, color, smell), homogeneity, preference test, pH, density, viscosity, dispersibility, and bacterial test.